2007
DOI: 10.1007/s12032-007-0030-z
|View full text |Cite
|
Sign up to set email alerts
|

The results of hypofractionated radiotherapy in 31 patients with high-grade gliomas

Abstract: In this prospective study, we investigated the effects of hypofractionated radiotherapy for patients with high-grade gliomas. About 31 patients with glioblastoma multiforme or anaplastic astrocytoma were studied between October 2003 and December 2004. Hypofractionated radiotherapy (3 Gy/fraction/day) was delivered to a total dose of 45 Gy in 15 fractions in 10 patients (32%) who had total excision before radiotherapy and to a total dose of 54 Gy in 18 fractions in 21 patients (68%) who had subtotal excision or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Sayin et al [24] reported on a prospective series of 31 patients with malignant glioma who were treated with HFRT using 45 Gy in 15 fractions after GTR (n510) or a dose of 54 Gy in 18 fractions after STR (n520). The MS was 8 months with an actuarial 1 year survival of 40%.…”
Section: Resultsmentioning
confidence: 99%
“…Sayin et al [24] reported on a prospective series of 31 patients with malignant glioma who were treated with HFRT using 45 Gy in 15 fractions after GTR (n510) or a dose of 54 Gy in 18 fractions after STR (n520). The MS was 8 months with an actuarial 1 year survival of 40%.…”
Section: Resultsmentioning
confidence: 99%
“…[8,11] Toward this end, hypoRT has emerged as an attractive option in terms of reducing the OTT as well as number of hospital visits by the patients and their care-givers. The outcomes with hypoRT regimens [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] have been comparable and not inferior to protracted conventionally fractionated schedules [ Table 3]. The optimal fractionation regimen of hypoRT is not yet clearly defined with diverse fractionation schedules prevalent worldwide [ Table 3].…”
Section: Discussionmentioning
confidence: 99%
“…This regimen is used not only in older age but also in patients with poor prognosis and unresectable tumours [19]. Hypofractionation showed glioblastoma patients to have a favourable response in terms of survival rate over the conventional fractionation [26] while other studies concluded that hypofractionation had similar results and tolerance comparable with conventional fractionation [27, 28]. …”
Section: The Role Of Radiotherapymentioning
confidence: 99%